Ultrasound Triggered Co‐Delivery of Therapeutic MicroRNAs and a Triple Suicide Gene Therapy Vector by Using Biocompatible Polymer Nanoparticles for Improved Cancer Therapy in Mouse Models. Issue 5 (5th March 2021) - Kumar, Sukumar Uday; Wang, Huaijun; Telichko, Arsenii V.; Natarajan, Arutselvan; Bettinger, Thierry; Cherkaoui, Samir; Massoud, Tarik F.; Dahl, Jeremy J.; Paulmurugan, Ramasamy
Abstract: Microbubbles (MBs) exhibit cavitation upon exposure to ultrasound (US), which creates opportunities to adopt them in new therapeutic approaches. The present study reports an efficient, translatable approach to precisely control the spaciotemporal delivery of therapeutic microRNAs (AmiR‐21 and miR‐100) and TK‐p53‐NTR triple therapeutic gene, co‐loaded in PLGA‐PEG‐PEI polymer nanoparticles (NPs) to tumor models of triple negative breast cancer (TNBC) and hepatocellular carcinoma (HCC) using US‐mediated targeted destruction of BR38 MBs. PLGA‐PEG‐PEI conjugated triblock co‐polymer NPs are synthesized and characterized for their physicochemical properties, and optimized for co‐loading of miRNAs and TK‐p53‐NTR. Quantitative in vivo imaging and ex vivo tissue analysis of 4T1 (TNBC) subcutaneous tumors in BALB/c mice reveal 19 ± 0.5% ( p  < 0.01) increase in delivery of miRNAs, and 48 ± 1.79% ( p  < 0.001) increase in delivery of TK‐p53‐NTR upon US treatment, which results to 48 ± 6.98% ( p  < 0.01) reduction in tumor growth as compared to contralateral tumors without US. This significantly increases the survival rate of animals as compared to pDNA control group. Similar treatment effects are observed in both TNBC and HCC tumor models. This novel combined therapeutic approach, entailing both miRNAs and suicide gene therapy has strong potential for future applications in cancer therapy. Abstract : Ultrasound‐mediated targeted destruction of Microbubbles (MBs) precisely control the spaciotemporal delivery of therapeutics to target tissues. This work presents the application of this non‐invasive translatable approach for the delivery of therapeutic microRNAs and TK‐p53‐NTR triple therapeutic gene, co‐loaded in PLGA‐PEG‐PEI conjugated polymer nanoparticles to improve GCV and CB1954 prodrugs therapy in tumor models of triple negative breast cancer and hepatocellular carcinoma.